HUBUNGAN STATUS GIZI DENGAN KEJADIAN HIPERTENSI PADA USIA 26 – 59 TAHUN DI RUMAH SAKIT PEKANBARU MEDICAL CENTER - Humairah, Anugerah; Puspa Anggraini, Shelly; Iqra Fikha, Idri; Jelsa Nabilah, Okta (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Non-communicable diseases (NCDs) that are the leading cause of death globally include cardiovascular diseases. The majority of cardiovascular diseases are caused by controllable risk factors, among which is hypertension. Hypertension is an increase in arterial blood pressure where systolic blood pressure is equal to or greater than 140 mmHg and/or diastolic blood pressure is equal to or greater than 90 mmHg. Hypertension is known as the